DESIGNING THE DOCHOME APPLICATION TO SUPPORT EXCELLENT SERVICE AT THE KANJURUHAN HOSPITAL NERVE POLYTECHNIC, MALANG REGENCY - Ainul Mutrofin; Wening Palupi Dewi (Journal of Hospital Management and Services, 2025)
Telehealth is the use of electronic information and telecommunications technology to treat patient health by medical personnel and doctors. Designing the DocHome application to support and improve excellent service at the Kanjuruhan Regional Hospital, Malang Regency. The method in this research is descriptive qualitative. In determining informants, researchers used a purposive sampling technique that met the inclusion and exclusion criteria with 4 informants. Data collection techniques use interview and observation techniques. The data analysis carried out was data reduction, data presentation and drawing conclusions. The data validity test in this research is Data Triangulation. Neurology clinic services are almost the same as the clinic services at the Kanjuruhan District Hospital, Malang Regency. What is mandatory in the neurology clinic is that patients are required to measure the patient's blood pressure, because the most important thing needed by a neurologist is the patient's blood pressure. Based on the research results, it was concluded that the use of technology could especially be applied in the Kanjuruhan Regional Hospital's neurology clinic.